KAJIAN HARA DAUN TANAMAN KARET : PERUBAHAN KEBIJAKAN PEMUPUKAN SLOW RELEASE KE FAST RELEASE - Priyo Adi Nugroho (Institut Teknologi Sawit Indonesia, 2020)
The policy change in application of fertilizer type is the common matter in the plantation company. A leaf nutrient content study of immature rubber trees that applied slow release (SRF) and fast release (FRF) fertilizer has been conducted in Sungei Putih Research Centre. The method of this study followed a descriptive-analysis method by comparing the content of N, P, K and Mg on the leaf of immature rubber trees under application of SRF and FRF. The results indicated that N leaf content with SRF application significantly higher (P<0.01) than FRF consecutive 3.15% and 2.93%. The similar circumstance also occurred in P leaf content i.e. 0.25% and 0.19% respectively. Conversely, K and Mg content in SRF application was significantly lower than FRF (P<0.01). K and Mg content was 0.94% and 0.27% in SRF meanwhile in FRF, K and Mg content was 1.2% and 0.33%. The nutrient status of N and P in SRF application was better compared to in FRF. On the other hand the similar condition did not appear in nutrient status of K and Mg. The status of K in SRF application was not better other than FRF application. In the meantime there was no different of Mg status between SRF and FRF application.